PENGARUH EFEKTIVITAS PEMBELAJARAN DARING TERHADAP PRESTASI BELAJAR PESERTA DIDIK DALAM MATA PELAJARAN AQIDAH AKHLAK - Sobandi, Ani Anriani; Inayah, Asti (Prodi PAI IAILM Suryalaya, 2021)
The research aims to know possitive effects of online learning effectiveness on student achievements in MTs Serba Bakti Suryalaya. The used methode of this research is descriptive method through quantity approach with a population at 510 people, a sample of 26 people by using data collection technique such as questionnaire, observation, and documentation. To test variable x and y it’s done by determining mean value that interpreted by using interpretation data classification, and to relationship between varible x and y by using Rank Spearman correlation analysis technique. Based on data processing result, it’s obtained that the influence of online learning effectiveness on student achievement in MTs Serba Bakti Suryalaya have significant possitive effects with low category, it’s proven that rs= 0,23 is on interval 0,21 – 0,40 and t hitung (34,92) is more than t tabel (1, 711). The effectiveness of online learning determines student achievement by 53% and 47% is determined by other factors. It’s suggested for other researchers to do research by learning other factors that take effect to student achievement.